2018
DOI: 10.1080/07435800.2018.1431275
|View full text |Cite
|
Sign up to set email alerts
|

Occult urolithiasis in asymptomatic primary hyperparathyroidism

Abstract: Occult urolithiasis is present in about one-fifth of patients with asymptomatic PHPT and is associated with higher urinary calcium and 1,25(OH)D. Given that most patients will not have occult urolithiasis, targeted imaging in those most likely to have occult stones rather than screening all asymptomatic PHPT patients may be useful. The higher sensitivity of urinary calcium versus 1,25(OH)D suggests screening those with higher urinary calcium may be an appropriate approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 50 publications
1
17
0
2
Order By: Relevance
“…18,19 In our series, biochemical parameters did not differ significantly between 'stone formers' and 'nonstone formers' although other authors have demonstrated a higher risk of stone formation in patients with high urinary calcium levels. 15,20 Cassibba and colleagues, 21 showed that in patients with PHPT, overt nephrolithiasis is associated with higher levels of serum calcium and PTH confirming the role of PHPT as a risk factor with further suggestions that silent nephrolithiasis helps to identify a more active and severe form of disease and these patients meet surgical indication more frequently than PHPT without stone disease. In contrast with these suggestions, we could not characterize the predictive risk factors for stone formation in PHPT, except that it was more prevalent in the male population.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…18,19 In our series, biochemical parameters did not differ significantly between 'stone formers' and 'nonstone formers' although other authors have demonstrated a higher risk of stone formation in patients with high urinary calcium levels. 15,20 Cassibba and colleagues, 21 showed that in patients with PHPT, overt nephrolithiasis is associated with higher levels of serum calcium and PTH confirming the role of PHPT as a risk factor with further suggestions that silent nephrolithiasis helps to identify a more active and severe form of disease and these patients meet surgical indication more frequently than PHPT without stone disease. In contrast with these suggestions, we could not characterize the predictive risk factors for stone formation in PHPT, except that it was more prevalent in the male population.…”
mentioning
confidence: 96%
“…Moreover it also raises the issue of use of routine imaging of the renal tract in these patients as undetected urolithiasis may lead to infection, urinary tract obstruction and loss of renal function as evidenced by elevated creatinine and eGFR in our patients. Urolithiasis alone may not contribute to the decline in renal function 15 but this may also be related to the extent and duration of hypercalcaemia. 16,17 The best method for diagnosing renal tract stones remains debatable but CT scans appear to be more sensitive as evident from our and other studies.…”
mentioning
confidence: 99%
“…PHPT is characterized by elevated serum PTH concentration and hypercalcemia [8], with varying degrees of severity from asymptomatic to hypercalcemic crisis [9,10]. Among pregnant patients with PHPT [11], 80% develop nausea, vomiting, frequent (nocturnal) urination, which are overlapped with normal physiological reactions during pregnancy, and would be easily overlooked, complicating or delaying the diagnosis of PHPT [11].…”
Section: Clinical Manifestations and Diagnosis Of Pregnant Patients With Phptmentioning
confidence: 99%
“…Симптомы со стороны костной системы -патологические переломы, деформации скелета, болевой синдром. В классическом варианте osteitis fibrosa cystica выглядит как «бурые» опухоли, литические поражения, субпериостальная резорбция фаланг пальцев и костные кисты [26,27].…”
Section: специфические аспекты первичного гиперпаратиреозаunclassified